Trusted to share or tempted to hoard? Unpacking employee knowledge hiding through the interplay of leader trust and knowledge psychological ownership - Zhang, Wei; Leng, Shunying; Ran, Hao (Frontiers in Psychology, 2025)
IntroductionAnchored in Social Exchange Theory, Conservation of Resources Theory, Affective Events Theory, and Psychological Ownership Theory, this study develops an integrated model linking leader trust, job satisfaction, and knowledge hiding, while positioning knowledge psychological ownership (KPO) as a contextual boundary condition.MethodsSurvey data were collected from 518 matched leader-employee dyads across 17 Chinese knowledge-intensive firms in IT services, pharmaceutical R&D, high-end equipment manufacturing, and financial consulting. Structural equation modeling combined with PROCESS bootstrap analysis was employed to test the hypothesized relationships.ResultsConfirmatory-factor-analysis results indicate satisfactory discriminant validity for all four focal constructs. Empirical evidence shows that: (1) leader trust significantly curbs employee knowledge hiding (β = −0.31, p < 0.001); (2) job satisfaction partially mediates this relationship, with the indirect path accounting for 34 per cent of the total effect (β = 0.46, p < 0.001); and (3) KPO exerts a significant negative moderating influence on both the “leader trust → job satisfaction” path and the overall indirect effect, reducing the mediation coefficient from −0.17 to −0.06 under high-KPO conditions (β = −0.23, p < 0.001). These findings remain robust after controlling for organizational support, team competition, and industry heterogeneity.DiscussionThe study enriches the antecedent framework of knowledge hiding by foregrounding vertical trust, illuminating the dynamic tension between reciprocity motivation and resource-defence motivation, and clarifying the double-edged boundary role of psychological ownership. Practically, Organizations should enhance perceived trust through empowerment and feedback while implementing monitoring systems to cultivate knowledge-sharing climates.